Anti-staphylococcus aureus adaptive immunity is impaired in end-stage renal disease patients on hemodialysis: one-year longitudinal study - Darbouret- Hervier, Anne; Assi, Nada; Asensio, Marie-Jeanne; Bernabe, Beatrice; Lechevallier, Aurélie; Iantomasi, Raffaella; Rokbi, Bachra; Botelho-Nevers, Elisabeth; Ruiz, Sophie (Frontiers in Immunology, 2023)
Introduction Patients with end-stage renal disease (ESRD) display defects in adaptive and innate immunity, increasing susceptibility to infection. Staphylococcus aureus (S. aureus) is a major cause of bacteraemia in this population and is associated with increased mortality. More information on the immune response to S. aureus in these patients is needed to inform effective vaccine development. Methods A longitudinal prospective study was carried out at two medical centers and included 48 ESRD patients who started chronic hemodialysis (HD) treatment ≤3 months before inclusion. Control samples were taken from 62 consenting healthy blood donors. Blood samples were obtained from ESRD patients at each visit, on month (M) 0 (beginning of HD), M6 and M12. Around 50 immunological markers of adaptive and innate immunity were assessed to compare immune responses to S. aureus in ESRD patients versus controls to document the changes on their immune profile during HD. Results S. aureus survival in whole blood was significantly higher in ESRD patients than in controls at M0 (P=0.049), while impaired oxidative burst activity was observed in ESRD patients at all timepoints (P<0.001). S. aureus-specific immunoglobulin G (IgG) responses to iron surface determinant B (IsdB) and S. aureus α hemolysin (Hla) antigens were lower in ESRD patients than in healthy donors at M0 (P=0.003 and P=0.007, respectively) and M6 (P=0.05 and P=0.03, respectively), but were restored to control levels at M12. Moreover, S. aureus-specific T-helper cell responses were comparable to controls for IsdB but were impaired for Hla antigen at all timepoints: 10% of ESRD patients responded to Hla at M0, increasing to 30% at M12, compared with 45% of healthy donors. B-cell and T-cell concentrations in blood were significantly reduced (by 60% and 40%, respectively) compared with healthy controls. Finally, upregulation of Human Leucocyte Antigen-DR (HLA-DR) and C-C chemokine Receptor type 2 (CCR2) was impaired at M0 but was restored during the first year of HD. Conclusion All together, these results show that adaptive immunity was largely impaired in ESRD patients, whereas innate immunity was less impacted and tended to be restored by HD.